Longitudinal brain atrophy and mortality among people living in homelessness and precarious housing: A brief report of a longitudinal study - Jacob L. Stubbs; Andrea A. Jones; Kristina M. Gicas; Thalia S. Field; Manraj K. S. Heran; A. Talia Vertinsky; Donna J. Lang; Wayne Su; Allen E. Thornton; G. William MacEwan; Olga Leonova; Alexander Rauscher; et al. (PLoS ONE, 2026)
Background People living in homelessness or precarious housing experience more health challenges and earlier mortality than the general population. We characterized longitudinal changes in magnetic resonance imaging (MRI) measures of brain atrophy among people living without stable housing, evaluated risk factors associated with longitudinal atrophy, and assessed whether atrophy was associated with mortality. Methods Data was collected as part of an ongoing longitudinal observational study of people living without stable housing in Vancouver, Canada. We included 307 participants with two-or-more brain MRI scans over an average of 7.0 years. We evaluated select risk factors for brain atrophy and assessed whether brain atrophy was associated with mortality during the study. Results Across 307 participants and 1,173 brain MRI scans, alcohol dependence ( β = −0.053, 95% confidence interval [CI] −0.075 to −0.032, p < 0.0001) and higher cardiovascular risk scores ( β = −0.021, 95% CI −0.029 to −0.012, p < 0.0001) were associated with more rapid brain atrophy over time, and history of moderate or severe traumatic brain injury was associated with more atrophy at baseline ( β = −0.27, 95% CI −0.46 to −0.075, p = 0.0075). More brain atrophy at baseline was associated with mortality during the study, adjusting for age, sex, and other comorbidities (Hazard Ratio [HR] Quartile1 = reference; HR Q2 = 2.37, p = 0.035; HR Q3 = 4.01, p = 0.00032; HR Q4 = 4.91, p < 0.0001). Conclusions and relevance Alcohol dependence, cardiovascular risk, and traumatic brain injury may represent particularly important risk factors for brain atrophy, and brain atrophy is associated with mortality among people living without stable housing. Targeting these modifiable risk factors may improve brain health and functioning outcomes among people living without stable housing.